ISO 14649 (STEP-NC): New Standards for CNC Machining - Yusof, Yusri (International Journal of Integrated Engineering, 2010)
The changing economic climate has made global manufacturing a growing reality over the last decade, forcing companies from east and west and all over the world to collaborate beyond geographic boundaries in the design, manufacture and assemble of products. The ISO10303 and ISO14649 Standards (STEP and STEP-NC) have been developed to introduce interoperability into manufacturing enterprises so as to meet the challenge of responding to production on demand. The paper focuses on the use of this new standard to address the process planning and machining of turn/mill discrete components. Due to the complexity of programming these machines there is a need to model their process capability to improve the interoperable manufacturing capability in places such as turning centres. Finally a proposed computational environment for a STEP-NC compliant system for turning operations (SCSTO) is described. And supported by the specification of information models and constructed using a structured methodology and object-oriented methods. SCSTO was developed to generate a Part 21 file based on machining features to support the interactive generation of process plans utilizing feature extraction. A case study component has been developed to prove the concept for using the milling and turning parts of ISO14649 to provide a turn-mill CAD/CAPP/CAM environment.